Do Surgeons React?: A Retrospective Analysis of Surgeons' Response to Harassment of a Colleague During Simulated Operating Theatre Scenarios. Issue 2 (August 2018) - Gostlow, Hannah; Vega, Camila Vega; Marlow, Nicholas; Babidge, Wendy; Maddern, Guy
Abstract : Objective: To assess and report on surgeons' ability to identify and manage incidences of harassment. Background: The Royal Australasian College of Surgeons is committed to driving out discrimination, bullying, harassment, and sexual harassment from surgical training and practice, through changing the culture of the workplace. To eradicate these behaviors, it is first critical to understand how the current workforce responds to these actions. Methods: A retrospective analysis of video data of an operating theatre simulation was conducted to identify how surgeons, from a range of experience levels, react to instances of harassment. Thematic analysis was used to categorize types of harassment and participant response characteristics. The frequency of these responses was assessed and reported. Results: The type of participant response depended on the nature of harassment being perpetuated and the seniority of the participant. In the 50 instances of scripted harassment, active responses were enacted 52% of the time, acknowledgment responses 16%, and no response enacted in 30%. One senior surgeon also perpetuated the harassment (2%). Trainees were more likely to respond actively compared with consultants. Conclusion: It is apparent that trainees are more aware of instances of harassment, and were more likely to intervene during the simulated scenario. However, a large proportion of harassment was unchallenged. The hierarchical nature of surgical education and the surgical workforce in general needs to enable a culture in which the responsibility to intervene is allowed and respected. Simulation-based education programs could be developed to train in the recognition and intervention of discrimination, bullying, harassment and sexual harassment.